2016
DOI: 10.1007/s00405-016-4144-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the CXCL12/CXCR4 chemokine axis predicts regional control in head and neck squamous cell carcinoma

Abstract: Expression of the CXCL12/CXCR4 chemokine axis has been related with the appearance of metastatic recurrence survival, including regional and distant recurrence, in patients with head and neck squamous cell carcinoma (HNSCC). RT-PCR was used to determine mRNA expression levels of CXCL12 and CXCR4 in biopsy tumor samples in 111 patients with HNSCC. Five-year regional recurrence-free survival for patients with low CXCR4 expression (n = 39, 31.5 %) was 97.4 %, for patients with high CXCR4/high CXCL12 expression (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Leon et al. ( 53 ) also found that low CXCL12 expression levels are significantly related to a high-risk of recurrence of HNSCC. In our study, no abnormal expression of CXCL12 was found in HNSCC tissues.…”
Section: Discussionmentioning
confidence: 95%
“…Leon et al. ( 53 ) also found that low CXCL12 expression levels are significantly related to a high-risk of recurrence of HNSCC. In our study, no abnormal expression of CXCL12 was found in HNSCC tissues.…”
Section: Discussionmentioning
confidence: 95%
“…In our study SDF-1 was on average lower in p16 positive tumours and no association between CXCR4 expression and p16 could be found. A more complex prognostic pattern for SDF-1 and CXCR4 is suggested from a study on 111 HNSCC patients who were treated with surgery, surgery plus postoperative RT/RT-CT or with primary RT/RT-CT [58] . In addition, Clatot and colleagues [59] found that lower SDF-1 expression determined by PCR in tumour specimen of 71 HNSCC patients was correlating with worse disease-free survival and cancer specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, targeting the chemokine receptor 4 (CXCR4) has emerged as a promising approach in cancer treatment. CXCR4 overexpression in HNSCC primary tumors associates with a higher risk of developing loco-regional recurrences and distant metastases after treatment and worse overall survival [ 7 , 8 ]. Moreover, preclinical and clinical data suggest that this chemokine pathway contributes to a resistant phenotype [ 8 ].…”
Section: Introductionmentioning
confidence: 99%